Politics and constitution making in India and Pakistan - Barua, B. P. (New Delhi, 1984)
This book is a study of the relationship between politics and constitution-making in two major countries of South Asia, namely, India and Pakistan, with special reference to the period 1919-1956. Although there is no dearth of literature on the constitutional history of India and Pakistan, few scholars have discussed and examined the interplay of politics, political theories and constitution making in the above countries. The author has examined the Western constitutional ideas, political beliefs and attitudes. Side by side, he has focused his attention on the political ideas, beliefs, attitudes and view points of the leading Muslim thinkers as well as some representative Indian thinkers, like Gandhi, M.N. Roy, Subhash Chandra Bose and Jayaprakash Narayan. In addition, he has attempted to relate the ideas of other important thinkers and leaders to the constitutional evolution and constitution-making in India and Pakistan. Finally, he has analysed and assessed the major socio-economic and political forces which had shaped constitution-making in both countries.
Keywords: India-Constitutional history